Criações didáticas: um estudo sobre os materiais didáticos alternativos em pesquisas em nível de mestrado e doutorado no brasil no período de 2010 a 2020 - DUARTE, Wellington Evangelista (Universidade Federal do Pará, 2023)
The present thesis has by objective analyze the relationships of internal didactic transposition in the didactic creations involving alternative teaching materials as a teaching and learning resource in research at master's and doctoral levels in Brazil from 2010 to 2020. To achieve this objective, we rely on the theoretical aspect of internal didactic transposition and didactic creations, having as a guiding question "can alternative didactic materials evidence didactic creations susceptible to the institutionalization of knowledge from a process of internal didactic transposition?" he research methodology used was qualitative meta-analysis, with the production of data being carried out in two national repositories: in the Brazilian Digital Library of Theses and Dissertations and in the Theses Bank of the Coordination for the Improvement of Higher Education Personnel, in which the research in which the materials were used from a teaching practice in the early years of elementary school. From our analyses, we emphasize that it is possible to evidence a didactic creation from manipulative activities, as long as this text of knowledge is able to contemplate some particularities so that this use leads the student to meet his construction with knowledge, and even if the teacher manages to implement its text of knowledge in the two moments of TDI, causing the didactic creation, this movement alone does not guarantee the institutionalization of the knowledge involved in the proposed activity, as it permeates the way the material is conceived as a didactic tool by the teacher to teach a given mathematical object . Therefore, it is worth mentioning that the use of any material requires didactic intention, because without defined objectives, there is no guarantee of learning.